Strengthening The Islamic Identity Of Indonesian Migrant Children In Malaysia Through Learning The Al-Quran - Della Monica; Kuliyatun Kuliyatun; Iswati Iswati; Siti Nur Azizah; Atika Putri Chairani; Azzahra Arimbi Kamila; Avrielle Mauliaraudhah Farmudya (Universitas Muhammadiyah Purwokerto, 2024)
This research examines efforts to strengthen the Islamic identity of Indonesian immigrant children in Malaysia through learning the Koran through International Volunteer Delegations. Cross-border immigration often brings new challenges, including maintaining religious and cultural identity. The focus of this research is how learning the Koran can be an effective tool in strengthening the Islamic identity of Indonesian immigrant children in Malaysia. The research method used is qualitative research with a case study approach. Data was collected through participant observation, interviews, and document analysis. The respondents of this research were children of Indonesian immigrants in Malaysia and educators involved in the Al-Quran learning process. The research results show that Al-Quran learning is essential in strengthening the Islamic identity of Indonesian immigrant children in Malaysia. Through learning the Koran, children can gain a deeper understanding of Islamic teachings, moral values, and Islamic culture. They may also develop a sense of pride in their religious and cultural identity. In conclusion, learning the Koran can be an effective means of strengthening the Islamic identity of Indonesian immigrant children in Malaysia. However, strong support is needed from various parties, including families, schools, and the environment, to ensure the sustainability and effectiveness of this effort.